Development of a Nonenzymatic Kinetic Resolution of α-Allenic Alcohols - Wang, Yan; Hoen, Rob; Hong, Ran (Synlett, 2012)
This personal viewpoint lays out the development of a silver-catalyzed kinetic resolution of α-allenic alcohols inspired by the biomimetic synthesis of natural products. The corresponding selectivity factor (s) indicates that this resolution protocol can deliver chiral allenic alcohols and 2,5-dihydrofurans in high enantioselectivity with synthetically applicable isolated yields. The broad substrate scope makes it an attractive approach for building synthetically useful chiral building blocks. From the recent progress in allene chemistry, silver was considered as an anion metathesis reagent to prepare highly efficient Au catalysts. Our discovery of the unique reactivity of a chiral silver phosphate should stimulate more interesting discoveries in this field.
Keywords: kinetic resolution; allenic alcohol; chiral silver phosphate; cycloisomerization; natural products